2019
DOI: 10.4103/npmj.npmj_59_19
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of prevalent Hepatitis B virus genotypes in Zaria, Nigeria

Abstract: Background: Hepatitis B virus (HBV) is hyperendemic in Nigeria. Available literature reveal genotype E as being predominant in West Africa. This study aimed at identifying the current pattern and prevalent genotypes of HBV in Zaria, Nigeria. Materials and Methods: Four millilitre of blood was collected in ethylenediaminetetraacetic acid-container from each of 165 HBV surface antigen-positive participants recruited purposively from the gastroenterology clinic from May to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
3
10
2
Order By: Relevance
“…Some investigators have also suggested that patient's fulminant hepatitis is more frequent in patients with genotype D infection [41], with higher HBeAg positivity seen in patients infected with genotype D adds credence to this assertion. Interestingly, HBV mono-genotype infection was shown to dominate over mixed genotype infection that opposed to a study conducted in speci c parts of Africa in which HBV mixed-genotype infections are predominant [42]. The observed HBV mixed-genotypes infection in this study may be due to possible recombination between genotypes or migration ows.…”
Section: Discussioncontrasting
confidence: 93%
“…Some investigators have also suggested that patient's fulminant hepatitis is more frequent in patients with genotype D infection [41], with higher HBeAg positivity seen in patients infected with genotype D adds credence to this assertion. Interestingly, HBV mono-genotype infection was shown to dominate over mixed genotype infection that opposed to a study conducted in speci c parts of Africa in which HBV mixed-genotype infections are predominant [42]. The observed HBV mixed-genotypes infection in this study may be due to possible recombination between genotypes or migration ows.…”
Section: Discussioncontrasting
confidence: 93%
“…Our nding of single-genotype predominance also agrees with a study in Egypt using INNO-LiPA, which reported that 87% of patients harboured singlegenotype infection, most commonly genotype D [25]. However, these ndings contrast with those from Iraq and Nigeria, in which mixed-genotype infections were documented in 75 and 82.6% of patients, respectively [19,26].…”
Section: Discussionsupporting
confidence: 90%
“…This method appears to have higher sensitivity for detecting mixed genotypes, and it is simple and cost-effective for large population studies with a high accuracy rate of 93% [17]. [18][19][20][21][22]. These ndings con rmed the variability of different methods of HBV-DNA detection in relation to HBsAg positivity, and that the variability could be in uenced by whether patients have chronic infection [23].…”
Section: Discussionmentioning
confidence: 98%
“…This is in concordance with findings from Taiwan, in which single genotype B infection was most common 19 , and with a study in Egypt, which reported that 87% of patients harbored single-genotype infection, most commonly genotype D 20 . On the contrary, studies from Iraq and Nigeria documented that mixed-genotype infections were present in 75% and 82.6% of patients, respectively 21 , 22 . When mixed and single infections were considered together, we found that genotype D had the highest prevalence, followed by genotypes C, E, C/D, C/E, C/D/E, A/D, D/E, A, B, A/E, B/E, and A/D/C.…”
Section: Discussionmentioning
confidence: 90%